Investigation of the effect of hydroxycitric acid on urinary calcium oxalate risk factors for kidney stone formation in artificial urine: theoretical modelling and in vitro crystallisation experiments - Ahmed, Amouna (Department of Chemistry, 2020)
Nephrolithiasis, or urolithiasis, commonly known as kidney stones, is a common medical problem. Kidney stones are composed of different mineral types. Calcium Oxalate is the most common kind of stone. The principal aim of this research was to establish whether hydroxycitrate (HCA) affects and/or inhibits calcium oxalate crystallisation. A three-pronged approach was adopted, involving the determination of thermodynamic binding constants for Ca, Mg and Zn-HCA complexes, theoretical modelling of HCA-complex formation in artificial urine and in vitro crystallisation experiments. A potentiometric analysis was conducted to determine thermodynamic binding constants. These were included in the database of the JESS computer program to model the effect of HCA on the urinary supersaturation of calcium salts. A 1 mM HCA concentrations successfully decreased the concentration of ionised calcium and hence the urinary supersaturation of calcium salts. The solution structures of H+ , Ca 2+, Mg 2+, and Zn 2+ -HCA complexes were investigated using 1H-NMR. For protonation, the results showed that the pKa values were too close to resolve and that several microstates were in rapid exchange. Similarly, for the metal complexes, several species were found to be in rapid exchange. Crystallisation experiments were conducted in artificial urine, to determine the effect of HCA on the thermodynamics and kinetics of crystallisation of calcium oxalate, which is the most common component of kidney stones. The effect of HCA on calcium oxalate metastable limit (MSL) and crystallisation kinetics were measured. The results confirmed those predicted by theoretical modelling. The MSL was significantly affected by 1 mM HCA. Also, 1 mM HCA increased the rate of CaOx crystallisation. Both these effects are favourable and decrease the risk of in vivo crystal and stone formation. This augurs well for the potential application of HCA as a therapeutic agent in the management of kidney stone disease. Such an outcome needs to be tested in human trials.